2022
DOI: 10.30998/jurnalpkm.v5i3.8052
|View full text |Cite
|
Sign up to set email alerts
|

Budidaya Padi Organik untuk Penyediaan Pangan yang Sehat dan Keberlanjutan Produktivitas Lahan Pertanian

Abstract: Moutong merupakan salah satu kelompok tani yang aktif dalam budidaya padi sawah. Masalah yang dihadapi dalam budidaya padi adalah: (1) kurang tersedianya pupuk organik, (2) rendahnya produktivitas padi yang dihasilkan, (3) serangan hama dan penyakit, dan (4) manajemen organisasi kelompok masih lemah. Program Kemitraan Masyarakat bertujuan untuk membantu petani menerapkan teknik menanam padi sawah organik, mengembangkan input dan bahan produksi untuk mengendalikan hama dan penyakit secara ekologis, dan menyedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
0
0
1
Order By: Relevance
“…Pengendalian hama penyakit lebih mudah dilakukan dalam kegiatan pemanfaatan pekarangan dengan tanaman sayuran. Pada lahan pekarangan yang sempit pengendalian hama dan penyakit dilakukan secara manual sehingga penggunaan bahan kimia dapat dibatasi, sehingga sayuran yang dihasilkan di pekarangan lebih sehat untuk dikonsumsi, karena merupakan sayuran organik (Tangkesalu et al, 2022). e. Pemanenan Sayuran perdu yang dipetik daunnya sudah dapat dipanen pada umur 35 -40 hari.…”
Section: Pelaksanaan Penyuluhanunclassified
“…Pengendalian hama penyakit lebih mudah dilakukan dalam kegiatan pemanfaatan pekarangan dengan tanaman sayuran. Pada lahan pekarangan yang sempit pengendalian hama dan penyakit dilakukan secara manual sehingga penggunaan bahan kimia dapat dibatasi, sehingga sayuran yang dihasilkan di pekarangan lebih sehat untuk dikonsumsi, karena merupakan sayuran organik (Tangkesalu et al, 2022). e. Pemanenan Sayuran perdu yang dipetik daunnya sudah dapat dipanen pada umur 35 -40 hari.…”
Section: Pelaksanaan Penyuluhanunclassified
“…Research by Nuraini et al (2015) with the aim of increasing farmers' knowledge and skills in developing agriculture on dry land with the LEISA system, showed that in general, the extension program had succeeded in increasing farmers' understanding from not knowing to knowing and skilled and expressed interest in using the LEISA system by utilizing local potential for agricultural production on dry land, and transmitting their knowledge to other farmers. The application of LEISA to produce healthy food and sustainability of agricultural land productivity in Sigi Regency -Central Sulawesi, conducted by Tangkesalu et al (2021), succeeded in having a significant positive effect on farmers, namely reducing the use of inorganic fertilizers and chemical pesticides by using organic fertilizers (compost) and biorational pesticides (bio-fungicides) developed by farmers themselves. The training on LEISA rice cultivation showed that the communities involved in this activity could adopt and apply the technology in their farms.…”
Section: Introductionmentioning
confidence: 99%
“…Stopping the use of synthetic chemicals in organic farming is a serious problem for farmers, and apart from long-standing habits, organic farming can also reduce yields if not handled properly. (Tangkesalu et al, 2022)The use of organic fertilizers can reduce the use of chemical fertilizers which people currently use in large quantities and buy at expensive prices. (Hadid et al, 2022) Furthermore, organic farming systems do not only focus on the use of natural materials, but holistically strive to develop and improve healthy biodiversity, including biodiversity, biological cycles and soil biological activity.…”
Section: Introductionmentioning
confidence: 99%